Reference ranges of handgrip strength from 125, 462 healthy adults in 21 countries: a prospective urban rural epidemiologic (PURE) study. Issue 5 (12th April 2016) - Leong, Darryl P.; Teo, Koon K.; Rangarajan, Sumathy; Kutty, V. Raman; Lanas, Fernando; Hui, Chen; Quanyong, Xiang; Zhenzhen, Qian; Jinhua, Tang; Noorhassim, Ismail; AlHabib, Khalid F; Moss, Sarah J.; et al.
Abstract: Background: The measurement of handgrip strength (HGS) has prognostic value with respect to all‐cause mortality, cardiovascular mortality and cardiovascular disease, and is an important part of the evaluation of frailty. Published reference ranges for HGS are mostly derived from Caucasian populations in high‐income countries. There is a paucity of information on normative HGS values in non‐Caucasian populations from low‐ or middle‐income countries. The objective of this study was to develop reference HGS ranges for healthy adults from a broad range of ethnicities and socioeconomically diverse geographic regions. Methods: HGS was measured using a Jamar dynamometer in 125, 462 healthy adults aged 35‐70 years from 21 countries in the Prospective Urban Rural Epidemiology (PURE) study. Results: HGS values differed among individuals from different geographic regions. HGS values were highest among those from Europe/North America, lowest among those from South Asia, South East Asia and Africa, and intermediate among those from China, South America, and the Middle East. Reference ranges stratified by geographic region, age, and sex are presented. These ranges varied from a median (25 th –75 th percentile) 50 kg (43–56 kg) in men <40 years from Europe/North America to 18 kg (14–20 kg) in women >60 years from South East Asia. Reference ranges by ethnicity and body‐mass index are also reported. Conclusions: Individual HGS measurements should be interpreted using region/ethnic‐specific reference ranges.